The association between COMT rs4680 and 5-HTTLPR genotypes and concussion history in South African rugby union players. Issue 8 (18th April 2018) - Mc Fie, Sarah; Abrahams, Shameemah; Patricios, Jon; Suter, Jason; Posthumus, Michael; September, Alison V.
ABSTRACT: The objective was to investigate the relationship between Catechol-O-methyltransferase ( COMT) rs4680 and serotonin-transporter-linked polymorphic region (5-HTTLPR) genotypes with concussion history and personality traits. Rugby players ("all levels": n = 303), from high schools ("junior", n = 137), senior amateur, and professional teams ("senior", n = 166), completed a self-reported concussion history questionnaire, Cloninger's Tridimensional Personality Questionnaire, and donated a DNA sample. Participants were allocated into control (non-concussed, n = 140), case (all) (previous suspected or diagnosed concussions, n = 163), or case (diagnosed only) (previous diagnosed concussion, n = 140) groups. COMT rs4680 Val/Val genotypes were over-represented in controls in all levels ( P  = 0.013, OR:2.00, 95% CI:1.15–3.57) and in juniors ( P  = 0.003, OR:3.57, 95% CI:1.45–9.09). Junior Val/Val participants displayed increased "anticipatory worry" ( P  = 0.023). The 5-HTTLPR low expressing group was under-represented in controls when all levels were considered ( P  = 0.032; OR:2.02, 95% CI:1.05–3.90) and in juniors ( P  = 0.021; OR:3.36, 95% CI:1.16–9.72). Junior 5-HTTLPR low and intermediate expressing groups displayed decreased "harm avoidance" ( P  = 0.009), "anticipatory worry" ( P  = 0.041), and "fear of uncertainty" ( P  < 0.001). This study provides preliminary indications that personality associated genetic variants can influence concussion in rugby.